Review of acoustic comfort evaluation in dwellings—part I: Associations of acoustic field data to subjective responses from building surveys. Issue 2 (June 2018) - Vardaxis, Nikolaos-Georgios; Bard, Delphine; Persson Waye, Kerstin
Acoustic comfort is a concept hardly described in the literature. But it has been used in engineering typically to refer to low noise or annoyance in order to invoke no discomfort. Current standardized methods for airborne and impact sound reduction are deployed to assess acoustic comfort in dwellings. However, the measured sound pressure levels do not represent comfort. The latter should include further the human perception of the acoustic environment. Therefore, this article reviews studies that approached acoustic comfort through the association of objective and subjective field data, combining in situ acoustic measurements and survey responses from residents. We evaluated the studies using Bradford Hill's criteria. Most researches focus on self-reported noise annoyance while some others on satisfaction responses. Many studies were found incomprehensibly described: often vital data of statistical evaluation or study design are lacking. The results indicate that noise is a significant issue in living environments, especially certain impact noise types. The use of extended low-frequency spectra down to 50 Hz was suggested for impact measurements in order to predict better self-reported noise response. Greater problems with low-frequency transmission are displayed in lightweight structures which perform inefficiently compared to heavyweight components. Harmonization of presented results and study design details should be taken into account for future articles.